2008
DOI: 10.1104/pp.108.119503
|View full text |Cite
|
Sign up to set email alerts
|

Light Regulation and Daytime Dependency of Inducible Plant Defenses in Arabidopsis: Phytochrome Signaling Controls Systemic Acquired Resistance Rather Than Local Defense

Abstract: We have examined molecular and physiological principles underlying the light dependency of defense activation in Arabidopsis (Arabidopsis thaliana) plants challenged with the bacterial pathogen Pseudomonas syringae. Within a fixed light/dark cycle, plant defense responses and disease resistance significantly depend on the time of day when pathogen contact takes place. Morning and midday inoculations result in higher salicylic acid accumulation, faster expression of pathogenesis-related genes, and a more pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
260
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(276 citation statements)
references
References 46 publications
(92 reference statements)
14
260
1
1
Order By: Relevance
“…Because there is evidence for overlap between SA, pathogen responses, and the regulation of flowering (Martínez et al, 2004), the requirement for LD-dependent SA accumulation in cat2 may reflect the coordination of H 2 O 2 -triggered lesions with the flowering program. Some aspects of pathogen responses interact with or are influenced by the phytochrome pathway (Genoud et al, 2002;Griebel and Zeier, 2008), while cryptochrome has been implicated in singlet oxygen-mediated effects (Danon et al, 2006). Thus, the daylength dependence of responses in cat2 (Fig.…”
Section: Peroxisomal H 2 O 2 Induces Biotic Defense Response Markersmentioning
confidence: 99%
“…Because there is evidence for overlap between SA, pathogen responses, and the regulation of flowering (Martínez et al, 2004), the requirement for LD-dependent SA accumulation in cat2 may reflect the coordination of H 2 O 2 -triggered lesions with the flowering program. Some aspects of pathogen responses interact with or are influenced by the phytochrome pathway (Genoud et al, 2002;Griebel and Zeier, 2008), while cryptochrome has been implicated in singlet oxygen-mediated effects (Danon et al, 2006). Thus, the daylength dependence of responses in cat2 (Fig.…”
Section: Peroxisomal H 2 O 2 Induces Biotic Defense Response Markersmentioning
confidence: 99%
“…Elicitor-induced hypersensitive cell death is a pathogen strategy for infection, whereas localized cell death at the site of infection is a plant defense strategy against pathogen attack [1,2]. Moreover, HR produced during some pathogen infection in plants has been recognized requiring the light [3,4]. However, further studies are needed to illustrate the underlying molecular mechanism of light-dependent HR cell death.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to HR development, the phyA and phyB mutants are also repressed in the salicylic acid (SA)-induced expression of the pathogenesis-related (PR) gene. The more severe effect of the phyA phyB double mutant on the SA-mediated pathway suggests that light perception has a cumulative effect on SA signaling and plant defense (27). Recent analysis has suggested a major role for PHYA PHYB in systemic immunity and a rather minor role in local defense response (27).…”
mentioning
confidence: 99%
“…The more severe effect of the phyA phyB double mutant on the SA-mediated pathway suggests that light perception has a cumulative effect on SA signaling and plant defense (27). Recent analysis has suggested a major role for PHYA PHYB in systemic immunity and a rather minor role in local defense response (27).Previously, we showed that light is required for resistance to Turnip Crinkle virus (TCV) in Arabidopsis (28). Resistance to TCV is dependent on the R protein HRT, which contains a coiled coil, nucleotide binding, and leucine-rich-repeat domain (29).…”
mentioning
confidence: 99%